Whatsapp Group Based Education to Improve Pregnant Women’s Knowledge About Stunting Prevention - Imro Atus Sholikhah; Erin Rizkiana (Poltekkes Kemenkes Semarang, 2023)
Background: Stunting is a chronic condition that describes stunted growth in children due to long-term malnutrition. Stunting not only causes delays in physical development but also threatens cognitive development which has an impact on reducing children's productivity in adulthood. Sriharjo Village is the village with the most cases of stunting with a percentage of 20.95%. as the Village with the highest number of stunting cases in Bantul district. Methods: This study used the Pre-Experiment research method with the type of one group pretest and post-test design. The sample consisted of 41 pregnant women in the first, second and third trimesters in Sriharjo Village, Imogiri Subdistrict. The samples were taken using purposive sampling. Analyzed using the Wilcoxon test